Improving Discipline Through Token Economy Method in Elementary School Students - Rahmawati, Adelia; Sholichah, Ima Fitri (INDONESIAN COUNSELING AND PSYCHOLOGY, 2025)
This study aims to evaluate the effectiveness of the token economy method in improving the discipline of first-grade students at Almadany Elementary School, Gresik. The subjects of the study were two students (AA and NS) who previously showed undisciplined behavior, such as not arranging their shoes neatly, often being late, and not being orderly when lining up. The intervention was carried out for six sessions, where students were given stickers as tokens every time they showed disciplined behavior. The tokens could be exchanged for prizes such as key chains or stationery. Data were collected through observation, teacher interviews, and documentation of behavioral changes, then analyzed descriptively using a behavior change table and the ABC (Antecedent–Behavior–Consequence) framework. The results showed a significant increase in discipline indicators: punctuality, cleanliness, neatness, and orderliness. The ABC analysis revealed that previous undisciplined behavior was caused by a lack of personal communication and an unclear reinforcement system. After the intervention, the relationship between behavior and its consequences became better understood, thus forming new positive habits. This study supports the behaviorist theory of positive reinforcement, and emphasizes the importance of a personal approach in learning strategies. Although limited to two participants and a short time, this study proves that token economy is effective in improving student discipline, especially in inclusive schools